Stratigraphy and paleontology of the Cloverly Formation (Lower Cretaceous) of the Bighorn Basin area, Wyoming and Montana - Ostrom, John H. (Peabody Museum of Natural History, Yale University, 2020)
The fiftieth anniversary edition of a landmark publication showcasing prehistoric North American landscapes and ecosystems, from a celebrated paleontologist at Yale University's Peabody Museum.